2020
DOI: 10.1097/ico.0000000000002315
|View full text |Cite
|
Sign up to set email alerts
|

Topical Voriconazole as Supplemental Treatment for Acanthamoeba Keratitis

Abstract: Purpose: Voriconazole was shown to inhibit ergosterol synthesis in various acanthamoeba species. The purpose of this study was to evaluate the clinical outcome of treatment with supplemental topical voriconazole in patients with acanthamoeba keratitis (AK). Methods: All patients who had been treated for AK with voriconazole 1% drops in conjunction with topical first-line antiacanthamoeba therapy composed of polyhexamethylene biguanide (PHMB) 0.02% and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 39 publications
0
23
0
1
Order By: Relevance
“…However, an assay study from 2019 reported that voriconazole was not cysticidal and that it antagonized the activity of both chlorhexidine and propamidine 34. Nonetheless, a 2020 retrospective case series reported resolution of AK in all 26 eyes treated with a combination of topical voriconazole 1%, PHMB 0.02%, and propamidine isethionate 0.1% followed for at least 3 months after cessation of therapy 35…”
Section: Voriconazolementioning
confidence: 99%
“…However, an assay study from 2019 reported that voriconazole was not cysticidal and that it antagonized the activity of both chlorhexidine and propamidine 34. Nonetheless, a 2020 retrospective case series reported resolution of AK in all 26 eyes treated with a combination of topical voriconazole 1%, PHMB 0.02%, and propamidine isethionate 0.1% followed for at least 3 months after cessation of therapy 35…”
Section: Voriconazolementioning
confidence: 99%
“…AK treatment also involves hourly topical application of combined drugs such as polyhexamethylene biguanide or chlorhexidine digluconate with propamidine isethionate or hexamidine. In addition, chloramphenicol or neomycin is commonly used to prevent bacterial infection 35–38 . Despite of aforementioned, these therapeutic approaches result in post‐therapy problems of drug resistance, side effects, and toxicity.…”
Section: Prevention and Treatment Of Akmentioning
confidence: 99%
“…In addition, chloramphenicol or neomycin is commonly used to prevent bacterial infection. [35][36][37][38] Despite of aforementioned, these therapeutic approaches result in post-therapy problems of drug resistance, side effects, and toxicity. Additionally, the combinational treatment strategy is mostly effective in early stages of infection, but it becomes ineffective after prolonged exposure.…”
Section: Prevention and Treatment Of Akmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that more than 80% of cases of Acanthamoeba keratitis occur in contact lens wearers. 3 Acanthamoeba exists in two forms, quiescent cyst and active trophozoite form. Under unfavorable conditions, trophozoites are encysted.…”
Section: Introductionmentioning
confidence: 99%